Nano-antivirals: A comprehensive review - Hussain, Fayyaz Salih; Abro, Naveed Qasim; Ahmed, Naseer; Memon, Saima Q.; Memon, Najma (Frontiers in Nanotechnology, 2022)
Nanoparticles can be used as inhibitory agents against various microorganisms including bacteria, algae, archaea, fungi, and huge class of viruses. Mechanism of action includes inhibiting the function of cell membrane/stop the synthesis of cell membrane, disturb the transduction of energy, production of toxic reactive oxygen species (ROS), inhibit or reduce RNA and DNA production etc. Variety of nanomaterials including different type of metallic, silicon and carbon-based nanomaterials, nanoarchitectures etc. has been successfully used against different viruses. Latest research strongly agrees that these nanoarchitectures-based virucidal materials (nano-antivirals) have shown activity is solid state as well, therefore very useful in the development of variety of products, for example fabric, high touch surfaces and others. This review thoroughly and critically identifies recently developed nano-antivirals and their products, nano-antiviral deposition methods on various substrates, and possible mechanisms of action. Considering the commercial viability of nano-antivirals, recommendations are made to develop scalable and sustainable nano-antiviral products with contact-killing properties.